PENGARUH MEDIA PENILAIAN TERHADAP HASIL BELAJAR SISWA BERBASIS GAME EDUKASI WORDWALL PADA MATA PELAJARAN SEJARAH INDONESIA DI KELAS XI SMA NEGERI 8 KOTA JAMBI T.A 2022/2023 - Harianja, Angelia; Agustiningsih, Nur (Universitas Batanghari Jambi, 2023)
This study aims to determine the influence of assessment media on student learning outcomes based onWordwall educational games in history subjects in class XI. The research carried out is a type of experimentalresearch using One – Group Pretest-Posttest Design (One Group Pretest-Postest). This research wasconducted in class XI Social Studies 5 with a total of 34 students. Based on the research conducted, the use ofIndonesian History lessons shows a significant influence compared to the use of conventional media. This canbe seen from the average score of the experimental class is greater than the average value of learning outcomesin the control class, overall the average score of the control class (pre-test) is lower than the average value ofthe control class (post-test) 75.5 < 64.5. In addition, students' attention focused on assessing learningoutcomes using Wordwall educational game media, affects students' understanding of the Indonesian Historysubjects taught to be optimal. Judging from the results of student tests that in all indicators student responsesthat reached an average of 81.01 out of 6 indicators consisting of 20 questions worked on, it means that theassessment media for student learning outcomes based on the educational game Wordwall affects studentlearning outcomes and is very effective.